Treatment of Millennial Generation Depression with Psychotherapy Methods: Analysis Study of Tafsir Al-JawÄhir fÄ« TafsÄ«ri Al-Qur'Än Al-KarÄ«m - Mariyah Ulfah; Yusuf Baihaqi; Rika Damayanti (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2023)
This research found that the millennial generation is considered vulnerable to mental disorders due to the increasingly rapid competition in this modern era. This often makes millennials feel stressed and depressed. One of the treatments is psychotherapy. Meanwhile, the object of his research refers to the interpretation in the style of knowledge, namely the interpretation written by Tantawi Jauhari. The type of research used in this study is qualitative and uses an analytic descriptive approach. It aims to find the unique side of the mufassir's interpretation in interpreting the Qur'an verses with a scientific style. So, in this case, the author tries to analyse the interpretation of Al-JawÄhir fÄ« TafsÄ«ri Al-Qur'Än al-KarÄ«m, which is related to psychotherapy in treating depression in the millennial generation. This research shows that the interpretation of Al-JawÄhir fÄ« TafsÄ«ri Al-Qur'Än al-KarÄ«m, which has an Ilmi style, has several opinions discussing psychology. The conclusion is that the treatment of millennial generation depression using psychotherapy methods, both psychological or psychiatric approaches and religious approaches, are two approaches that are interrelated and cannot be separated.